Encapsulamento da mangiferina em sílica mesoporosa: síntese e caracterização - Silva, Cássia Roberta Pontes (2017)
Silica-based mesoporous compounds have been widely used as carriers for the encapsulation of drugs because they have pores that have good chemical stability, are not harmful and have active sites that enable interaction with different substances. MCM-41 (Mobil Composition of Matter number forty one) and SBA-15 (Santa Barbara, amorphous number fifteen) are probably the most investigated materials of this type. SBA-15 has a hexagonal arrangement of amphiphilic block copolymers since MCM-41 is obtained by the long chain model action by alkylammonium surfactant molecules. Normally, pore diameter ranges from 2 to 6 nm for MCM-41 and between 4 and 13 nm for SBA-15. Mangiferin is a xanthone that has a high antioxidant action and is widely used for the treatment of cancer, antiallergic, anti-inflammatory, among other effects, but its low solubility in water causes it to need precursors so that it can be transported by the organism of beings Alive. In this work we suggest the encapsulation of maginferin in the hexagonal channels of SBA-15. Physical-chemical analyzes were performed, such as: FTI-R, nitrogen adsorption, electron microscopy, differential pulse voltammetry and DSC to investigate the interaction between these compounds. The FTI-R analysis showed the reduction of peaks for both SBA-15 and mangiferin, which indicates the interaction between these compounds, this result corroborated with the images obtained from the microscopy analysis that showed the hexagonal channels of the SBA-15 being maintained. In addition, the nitrogen adsorption analysis showed a 55% reduction in the pore volume of the SBA-15 indicating the presence of mangiferin in the pores. The differential pulse voltammetry analysis indicated a reduction of the mangiferin peaks after interaction with SBA-15, which makes it possible to affirm that the oxidative process of xanthone was increased due to the inclusion of mangiferin in the hydrophobic cavity of SBA-15, which promotes the increase of His solublicity. The DSC analysis indicated a decrease in the degration point.